The legacy of César Pacheco Vélez – Discussion group - De la Puente Candamo, José Agustín (1994)
César Pacheco Vélez (1929-1989) was a professor at Universidad del Pacífico, who recently published his book Essays of Sympathy. To comment the legacy of César Pacheco Vélez, and especially his last work, the Editorial Committee of the university convened a discussion group that we transcribe here. This was held at the Centre of Research of the same university and featured college professors of different generations who knew César Pacheco Vélez.